STUDIES ON THE HYDROGEN - ION CONCENTRATION AND DIGESTIVE ENZYMES IN THE ADULT OF PARAMECOPS FARINOSA (WIED.) (COLEOPTERA : CURCULIONIDAE) - SAHA, H.P.; PANDE, Y.D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
The hydrogenion concentration and distribution of digestive enzymes in the alimentary canal of adult Paramecops farinosa (Wied.) were studied pH of the gut of the insect showed wide variations. In fed condition the foregut was acidic (5.8 ± 0.17), the midgut slightly acidic to neutral (6.4 ±0.03) while hindgut was neutral to slightly alkaline (7.6±0.09). In the gut 9 enzymes, viz. amylase, cellobiase, maltase, melibiase, sucrase, trehalase, lactase, lipase and protease were found.